Statistical data on schizophrenia in Turkey - Karan, Doğan (The Turkish Journal of Pediatrics, 1962)
The intention of this paper is to present certain statistical data on schizophrenia in Turkey and to attempt to stimulate research into the state of schizophrenia in Turkey today. No previous paper has been published on this subject although the symptoms of schizophrenia in its early stages were discussed by the author and Dr. Adasal in a paper published in 1957.¹ The present paper will cover 189 cases of schizophrenia collected in Ankara between 1944 and 1950. A subsequent paper will correlate this material with data recorded during the years 1956 - 1962. It is obvious that complete and final deductions cannot be made from this amount of data but it is felt that the present inquiry is a necessary beginning to what will doubtless prove to be a lengthy investigation.